PNet for Dummies: An Introduction to Estimating Exponential Random Graph (P*) Models with PNet - HARRIGAN, Nicholas (Institutional Knowledge at Singapore Management University, 2007)
PNet for Dummies is intended to walk the new user through one complete estimation in PNet. It is not a comprehensive guide to PNet. Currently the most comprehensive guide to PNet is the PNet Users Manual. PNet for Dummies exists to help get the new user started, helping them overcome the most common initial barriers, so that they can begin exploring and experimenting with PNet themselves.